2017
DOI: 10.1016/j.jss.2016.09.024
|View full text |Cite|
|
Sign up to set email alerts
|

Exendin-4, a glucagon-like peptide-1 analogue, accelerates diabetic wound healing

Abstract: Ex4 accelerated excisional wound healing in subjects with diabetes. Glp-1R activation attenuates inflammatory response and enhances angiogenesis during the early proliferation phase of wound healing in diabetic subjects, while it enhances transforming growth factor-β/matrix metalloproteinase-mediated regeneration during the maturation phase. These results suggest that Ex4 could be used as a standard hypoglycemic agent in diabetic patients with wound injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Besides stimulation of proliferation and migration of endothelial cells in the wounded area, GLP1 increased also endothelial precursor cells thus facilitating capillary tube formation and neovascularization [104,106]. Finally, GLP1 appears to intervene also in the remodeling phase of the healing process by stimulating TGFβ1 production that, through the increased proliferation of fibroblasts, synthesis of collagen, stimulation of MMP activity, and remodeling of the extracellular matrix, is crucial for the healing event [104]. The accelerated and improved wound healing following inhibition of DPP4 in a murine excisional wound model was characterized by increased vascularization but also by improved dermal thickness of the wounded area [107].…”
Section: Dipeptidyl Peptidase 4 (Dpp4) Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides stimulation of proliferation and migration of endothelial cells in the wounded area, GLP1 increased also endothelial precursor cells thus facilitating capillary tube formation and neovascularization [104,106]. Finally, GLP1 appears to intervene also in the remodeling phase of the healing process by stimulating TGFβ1 production that, through the increased proliferation of fibroblasts, synthesis of collagen, stimulation of MMP activity, and remodeling of the extracellular matrix, is crucial for the healing event [104]. The accelerated and improved wound healing following inhibition of DPP4 in a murine excisional wound model was characterized by increased vascularization but also by improved dermal thickness of the wounded area [107].…”
Section: Dipeptidyl Peptidase 4 (Dpp4) Inhibitorsmentioning
confidence: 99%
“…A deeper knowledge of the involvement of DPP4 in reparative processes in wounded skin has prompted studies to investigate the potential for this target in the treatment of diabetic wounds. In excisional wound tissue of diabetic rats, it was shown that activation of GLP1 receptors reduced the formation of superoxide anions, ameliorated wound closure by reducing cytokines and inflammatory cells infiltration [104], and by inducing angiogenic activity through the increased expression of VEGF and HIF1α [105]. Besides stimulation of proliferation and migration of endothelial cells in the wounded area, GLP1 increased also endothelial precursor cells thus facilitating capillary tube formation and neovascularization [104,106].…”
Section: Dipeptidyl Peptidase 4 (Dpp4) Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GLP-1R has been identified in the skin of mice; in cultured skin cells, GLP-1 activates the mitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/ERK) pathway associated with cell proliferation, differentiation, and cytoprotection (List and He, 2006). In this regard, many recent studies have demonstrated the beneficial role of GLP-1 analogs such as exenatide and DPP-4 inhibitors such as vildagliptin in patients with diabetes (Lee and Lee, 2017), as well as promote ulcers healing on the feet (Long et al, 2018) and the healing of diabetic wounds in rodents (Roan et al, 2016). In addition, DPP-4 expression is increased in dermal fibroblasts of mouse muscle after skin damage (Schürmann et al, 2012) and is a prerequisite for fibroblast migration and proliferation, indicating the role of regional incretins in regulating fibroblast functions and, possibly, wound healing.…”
Section: Resultsmentioning
confidence: 99%
“…The improvement of vascular endothelial function restores impaired glucose tolerance by ameliorating insulin resistance in skeletal muscle (Kubota et al 2011). Interestingly, two-week administration of 0.5 μg/kg/day exenatide was shown to accelerate diabetic wound healing by increasing angiogenesis in the wound and the number of circulating EPCs (Roan et al 2017). Our recent, not yet published, work also demonstrates that 10 µg/kg exenatide can have beneficial effects on bone vascularisation in diabetic bone by acutely increasing blood flow to bone in db/db mice.…”
Section: Glp-1ras and Blood Flow To Bonementioning
confidence: 99%